Hydrogel-A Conceptual Overview - Dwivedi, Shakti (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Hydrogels have been used extensively in the development of the smart drug delivery systems. In 1960 Wichterle and Lim were discovered hydrogel of poly (2-hydroxyethyl methacrylate). Hydrogels constitute a group of materials which are used in numerous biomedical disciplines, and are still developing for new promising applications. Hydrogels are three-dimensional, hydrophilic, polymeric networks that can swell in water and hold a large amount of water while maintaining the structure. They can be classified in different way as like on the basis of their preparation, biodegradable properties, polymer, sensitivity to surrounding environment and also their application. In this review we are focused on conceptual points of hydrogels related to hygrogel types, their crosslinking, polymers, application, as well as developments.